Improving Waste Management Sustainability: The Role of Institutional Capacity and Program Objectives - Munawir, Abdillah; Rusdiyanto, Edi; Muna, Siti Umamah Naili; Yunandar; Ali, Farida; Ihsan, Mohammad (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
This research aims to analyze 1) waste management in terms of the institutional capacity aspect involved in waste management, and 2) analyze the objectives of the waste management program to overcome problems that occur in the sustainability of waste management. A qualitative approach was used by conducting a Focus Group Discussion with seven selected respondents and then analyzed using a quantitative approach using Interpretive Structural Modeling. The results show that the key factor from the relevant agencies, or the most crucial in determining the sustainability of waste management in Kambu District, Kendari City, is the Kendari City Cleanliness and Parks Service, which is assisted by government involvement in Kendari City. Therefore, waste management requires good institutional synergy to ensure the sustainability of waste managementby conducting activities based on program objectives in the environmental cleanliness improvement program as the key factor. This can increase community involvement by reducing the volume of waste, utilizing waste recycling, and reusing waste, which can increase people's incomes. Another important element to ensure sustainable waste management is the improvement and maintenance of waste management facilities and infrastructure.